OPTIMIZING THE TOUR GUIDE'S PROVISION OF INFORMATION THROUGH ONLINE MEDIA: OPTIMALISASI TOUR GUIDE DALAM PEMBERIAN INFORMASI MELALUI MEDIA ON-LINE - Yulianto, Irwan; Alvianna, Stella; Pandu Dinata, Krishna; Luisa Stefani, Agnes (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Tour guides play a crucial role during a vacation. Tour guides do more than only provide information about the tourist spots seen; they also educate foreign tourists who visit an area. The number of travel agents supplying guidance is growing, and they come in a variety of forms, including companies, institutions, individuals, and communities. Objective: This activity tries to solve marketing difficulties (by generating online marketing media) while also giving tourist training, particularly for tour guides, to community members. Method: This activity tries to solve marketing difficulties (by generating online marketing media) while also giving tourist training, particularly for tour guides, to community members. Results: The presence of a website/blog will enhance the number of users or consumers who use the services provided by the "A Day in Malang" Community in Malang Regency, East Java, Indonesia. Having a website or blog: Promotions were once limited to word-of-mouth, but with the introduction of online management, marketing has expanded. Conclusion: Tour guide techniques are improving and becoming more professional, both in terms of guiding services and POP (Tourism Operational Planning), allowing activities to be structured and directed in accordance with the schedule established or previously agreed upon.